Effects of nitrogen fertilizers on the bacterial community diversity and the weathering of purple mudstone in Southwest China - Li, Chunpei; Fan, Maopan; Wang, Xuan; Li, Xue; Zhao, Guang; Liu, Gangcai; Zhao, Jixia (Frontiers in Microbiology, 2023)
Rock weathering is crucial in the development of soil. Yet the role of bacteria in the fine particle-forming process of purple mudstone is not fully understood, especially under nitrogen fertilization. In this study, the particles (0.25 mm to 1 mm) of purple mudstone from Penglai Group (J3p) were selected as tested material. Two nitrogen fertilizers i.e. urea (U) and ammonium bicarbonate (AB), and four application levels (0, 280, 560, and 840 N kg∙ha-1) with 18 replications were designed in an incubation experiment. The weathering indices and bacterial community structure of the purple mudstone particles were investigated after 120 days of incubation. The results showed that the weathering indices of purple mudstone particles in the AB treatment were higher than that in the U treatment at the same fertilization levels and a reducing trend was observed with increasing nitrogen fertilizer levels under the same nitrogen fertilizer application types. The diversity of the bacterial community was extremely significantly altered by nitrogen fertilizer application (p < 0.01). The effect of nitrogen fertilizer application level on the diversity of the bacterial community (R2=0.34) was greater than that of nitrogen fertilizer application type (R2=0.20). Through stepwise regression analysis, the positive effects of nitrification of Nitrobacter (Nitrolancea) (R2=0.36), the Phosphorous-dissolving bacteria (Massilia) (R2=0.12), and N-NO3- (R2=0.35) on the weathering indices of J3p purple mudstone particles. Structural equation modelling indicated that nitrogen fertilizer application level affects the abundance of the dominant species at the genus level (Nitrolancea and Massilia), and key environmental factor (N-NO3-), which in turn accelerated the weathering indices (59 %). Our findings implies that the enhancements of nitrification of Nitrobacter (Nitrolancea) and of phosphorus solubilization of Phosphorous-dissolving bacteria (Massilia) by nitrogen fertilization are the key factor affecting weathering indices of J3p purple mudstone particles.